Insurance, Policy, Knowledge Level and Epidemiology As Factors Affecting Demand And Supply of Pharmaceutical Product - Cahaya, Noor; Pramestutie, Hananditia Rachma; Hati, Anita Kumala; Untari, Eka Kartika; Utami, Pinasti (Brawijaya University, 2022)
Fulfillment of drug availability is always a challenge from year to year and is determined by supply and demand issues for pharmaceutical drugs. Good management of drugs and pharmaceutical supplies is important in health services. This is related to the quality of health services and the efficiency and effectiveness of the budget. This review study aims to examine the factors that influence drug supply and demand simultaneously with a different perspective from other studies, namely, the focus is to simultaneously discuss the effects of health insurance financing schemes, registration regulations for pharmaceutical products and imports of pharmaceutical products, the level of pharmacist knowledge, changes in disease patterns, disasters, and wars on drug supply and demand. The research design that was used in this study is a narrative review. The data sources that were used are PubMed, Science Direct, Scopus, and Google Scholar. The inclusion criteria in this study are all research related to the demand for pharmaceutical supplies and drugsthat will be reviewed in the study, either in the form of original research, reviews, or reports. The results obtained articles consisting of 8 articles related to health insurance financing, 6 articles related to registration regulation of pharmaceutical products and import of pharmaceutical products, 5 articles related to pharmacist knowledge level, 3 articles related to changes in disease patterns, and 3 articles related to disasters and wars. Based on the 25 articles that were used as data in this study, it was found that the factors that influence the supply and demand of pharmaceutical supplies are health insurance financing, regulation of registration drug processes and imports of pharmaceutical products, level of knowledge of pharmacists as pharmaceutical service providers, changes in disease patterns, disasters, politics, and war.